Smooth Extubation and Smooth Emergence Techniques: A Narrative Review - Tiffany H. Wong; Garret Weber; Apolonia E. Abramowicz (Anesthesiology Research and Practice)
There is a paucity of literature on extubation technique and a lack of consensus regarding the definition of smooth extubation. This narrative review paper defines an ideal extubation, otherwise known as a “smooth extubation,” reviews perioperative criteria for extubation and risks and adverse events related to extubation, and explores various perioperative techniques that can be used to achieve a smooth extubation while caring for an uncomplicated patient without significant risk factors for extubation failure. In light of the evolving practice during the SARS CoV2 (COVID-19) pandemic to minimize aerosol generation and infection transmission, smooth extubation is particularly important.